2012
DOI: 10.1007/s11745-012-3730-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Enhances Vitamin E Status and Reduces Oxidative Stress Indicators in Sea Bass Larvae Fed High DHA Microdiets

Abstract: 22Docosahexaenoic acid (DHA) is an essential fatty acid necessary for many biochemical, 23 cellular and physiological functions in fish. However, high dietary levels of DHA 24 increase free radical injury in sea bass larvae muscle, even when vitamin E (α-25 tocopherol, α-TOH) is increased. Therefore, the inclusion of other nutrients with 26 complementary antioxidant functions, such as vitamin C (ascorbic acid, AA), could 27 further contribute to prevent these lesions. The objective of the present study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
46
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 72 publications
6
46
1
2
Order By: Relevance
“…The addition of vitamin C to sea bass ( Dicentrarchus labrax ) diets containing 5% docosahexaenoic acid were found to salvage vitamin E (Betancor et al, 2012), again showing the interactions between these two antioxidant vitamins. In humans, the rate of disappearance of vitamin E in response to oxidative stress is dependent on vitamin C status (Bruno et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…The addition of vitamin C to sea bass ( Dicentrarchus labrax ) diets containing 5% docosahexaenoic acid were found to salvage vitamin E (Betancor et al, 2012), again showing the interactions between these two antioxidant vitamins. In humans, the rate of disappearance of vitamin E in response to oxidative stress is dependent on vitamin C status (Bruno et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…However, at 24 h, GSH-Px activities were significantly inhibited, which may interfere with the decomposition of H 2 O 2 and result in over-production of Á OH. The highly reactive Á OH reacts with DNA by addition to double bonds of DNA bases and by abstraction of an H atom from the methyl group and 2 0 -deoxyribose of thymine (Cooke et al 2003), consequently leading to the significantly increased level of DNA damage at 24 h. However, the excessive ROS-induced lipid peroxidation at 24 h might be balanced to some extent by stimulating effects of monocrotophos on non-enzyme antioxidants such as vitamin E and vitamin C, which exist in the membrane or in plasma and protect lipoproteins from oxidation (Machlin and Bendich 1987;Betancor et al 2012). Thus, MDA concentrations did not exhibit a trend to increase even though the GSH-Px activities decreased.…”
Section: Discussionmentioning
confidence: 99%
“…This dramatic decrease in nonenzymatic free radical scavengers corroborates that these are actively involved in detoxification process of free radicals, protecting embryos against possible damages. Dietary vitamin E significantly decreased lipid peroxidation products in seabass larvae fed high DHA diets and oxidative stress indicators which were further reduced by dietary vitamin C supplementation (Betancor et al, 2012). In developing Dentex dentex larvae, dramatic collapse in vitamin E indicated that this vitamin was consumed rapidly at this stage in the process of quenching ROS and chain-breaking.…”
Section: Discussionmentioning
confidence: 96%
“…The harmful effects of ROS can be experienced as DNA damage, enzyme inhibition, structural protein degradation and unsaturated lipid peroxidation resulting in pathologies and alteration of normal development (Halliwell and Gutteridge, 2000). Pathological consequences of oxidative stress in fish include depleted growth rate, low survival, muscular dystrophy, anemia and liver degeneration (Betancor et al, 2012). Oxidative stress happens when the ROS generation rate is higher than the rate of their removal.…”
mentioning
confidence: 99%